Evaluation of the ergogenic properties of ginseng: an update - Bahrke, M. S.; Morgan, W. R. (Sports Medicine, 2000)
Ginseng has been used in the Orient for several thousand years as an 'adaptogenic' as well as a 'restorative' agent. It has been used to treat nervous disorders, anaemia, wakefulness, dyspnoea, forgetfulness and confusion, prolonged thirst, decreased libido, chronic fatigue, angina and nausea. Although the mechanisms underlying the alleged effects of ginseng remain to be elucidated, there is an extensive animal literature dealing with the effects of ginseng on the cardiovascular system, central nervous system, endocrine system, metabolism, and immune system. In our previous review dealing with the efficacy of ginseng, we concluded that while studies with animals show that ginseng, or its active components, may prolong survival to physical or chemical stress, there is generally a lack of controlled research demonstrating the ability of ginseng to improve or prolong performance in fatigued humans. In this review, we extend our earlier analysis on the potential efficacy of ginseng use in the enhancement of physical performance and modification of fatigue states. Our analysis reveals that published literature appearing since our earlier review has not resolved the equivocal nature of research evidence involving animals or humans. Also, the lack of unanimity in this research can be explained on the basis of various methodological problems such as inadequate sample size and lack of double-blind, control and placebo paradigms. In addition, the absence of acceptable approaches to the problem of 'sourcing', in concert with an absence of compliance data in human research, further complicates the interpretation of this research literature. Nevertheless, the use of ginseng continues to grow, and current sales are estimated to be over $US300 million annually. There is clearly a need for systematic research dealing with the efficacy of ginseng, and this research needs to take into account basic, fundamental design considerations if there is to be any hope of establishing whether or not ginseng possesses efficacy.